Analisis Kelengkapan Pengisian Identitas Pasien Pada Formulir Lembar Masuk Dan Keluar Pasien Rawat Inap Rumah Sakit Wangaya - Nuralim, Ristu Airul; Purwanti, Ika Setya; Adiputra, I Made Sudarma (Poltekkes Kemenkes Jambi, 2025)
Background: Incompleteness in filling out medical record files will result in the records contained being out of sync and the patient's previous health information being difficult to identify. This study aims to determine the completeness of filling in the patient's identity on the inpatient admission and discharge form. Method: The research method used is quantitative descriptive. The sample used was 237 medical records of inpatients in October taken by simple random sampling. Results: The research results showed that 152 sheets of the entry and exit summary forms were complete (64.14%) and 85 sheets of the entry and exit summary forms were incomplete (35.86%). The reason for the incomplete filling in of the patient's identity on the admission and discharge summary form is because the implementation of standard operational procedures has not been optimal. What the hospital needs to do next is carry out outreach regarding filling in patient identity and immediately implement electronic medical records. Conclusion: There are still incompleteness in filling in the medical resume for the identity of inpatients at Wangaya Hospital.